Implementation of voltage self-balanced 17-level switched capacitor MLI topology for solar PV systems - Paneti Anjaneya Vara Prasad; C. Dhanamjayulu (Results in Engineering)
This article describes the novel self-balanced switched capacitor multilevel inverter (SCMLI) for microgrid applications by utilizing the solar photovoltaic (PV) source. The proposed topology is the combination of corresponding controlled power switching devices and capacitors to enhance the expected output voltage by operating in charging mode and discharging mode based on the requirement. The high voltage gain, low device count, and the capacitor self-voltage balancing are the main constructional advantages of this topology. The proposed topology usages a lower number of switches to generate the required output voltage level at the load side with the help of the average level constant carrier pulse width modulation (PWM) technique. The soft handling of switches and the balancing of capacitor voltage are also done with this PWM technique. This proposed topology also had merits like having less voltage stress, cost, losses, and total harmonic distortion (THD) along with high efficiency. The assessment concerning the comparison of presented topology by some already existing SCMLI topologies has been done by the constructional and performance parameters. To validate these advantages of the Proposed topology, the simulation outcomes, as well as experimental outcomes are presented.